The openness-inflation puzzle: an asymmetric approach. Issue 2 (4th May 2022) - Shah, Irfan Ahmad; Lavanya, Ammu
ABSTRACT: The paper analyzes Inflation Openness (IO) relationship in an asymmetric framework using lag inflation, lag external debt and lag output growth as transition variables. Considering a Panel Smooth Transition Regression (PSTR) model with annual data of 41 developing countries for a period of 45 years from 1972 to 2016, we found a clear negative relationship between inflation and openness. This relationship becomes strong during periods of high inflation, high output growth and low external debt. We argue that though openness reduces inflation, its impact varies depending upon the state of the economy. We conclude that analysing the IO relationship using a linear framework may result in inaccurate and misleading outcomes.